Thermal grain boundary grooves formation in tungsten under recrystallization - Belyaeva, A.I.; Galuza, A.A.; Kolenov, I.V.; Savchenko, A.A. (Вопросы атомной науки и техники, 2017)
Tungsten has been chosen as the main candidate for plasma facing components (PFCs) due to its superior properties under extreme operating conditions in future nuclear fusion reactors such as ITER and DEMO. One of the serious issues for PFCs is the high heat load during transient events and disruption in the reactor. Recrystallization and grain size growth in PFC materials are undesirable changes in the materials, since the microstructure developed after recrystallization exhibits a lower mechanical strength and an increased surface roughening. The current work was focused on careful investigation of the thermal grooving at grain boundaries (GB) in tungsten surface under recrystallization (W-rс). Topography of GB thermal grooves in W-rc is studied by atomic force microscopy (AFM). The peculiarities of its profile formation and the main factors which effect on the profile of GB grooving were determined. It is the purpose of this paper to point out these factors. The nature of GB grooving was determined. Завдяки своїм унікальним властивостям вольфрам є основним кандидатом для конструкційних елементів, які повернені до плазми, у таких перспективних реакторах, як ITER та DEMO. Однією з важливих проблем для таких елементів є високе термічне навантаження при перехідних процесах та зривах плазми в реакторі. Рекристалізація та зростання розміру зерна в матеріалах елементів, які повернені до плазми, є небажаними, оскільки мікроструктура, що формується при рекристалізації, дає більш низькі механічні властивості та підвищену шорсткість. Ця робота присвячена дослідженню формування термічних канавок на границях зерен у вольфрамі при рекристалізації (W-rc). Топографія канавок термічного травлення (КТТ) у W-rc вивчена за допомогою атомної силової мікроскопії. Визначені особливості формування КТТ та основні фактори, що впливають на їх профіль. Метою даної роботи було вияснення цих факторів. З’ясована природа термічних канавок травлення. Благодаря своим уникальным свойствам вольфрам является основным кандидатом для обращенных к плазме конструкционных элементов таких перспективных реакторов, как ITER и DEMO. Одной из серьезных проблем для таких элементов является высокая термическая нагрузка при переходных процессах и срывах плазмы в реакторе. Рекристаллизация и увеличение размера зерна в материалах, обращенных к плазме элементов, являются нежелательными, поскольку микроструктура, формирующаяся при рекристаллизации, дает более низкие механические свойства и увеличенную шероховатость. Настоящая работа посвящена исследованию формирования термических канавок на границах зерен в вольфраме при рекристаллизации (W-rc). Топография канавок термического травления (КТТ) в W-rc изучена с помощью атомной силовой микроскопии. Определены особенности формирования КТТ и основные факторы, влияющие на их профиль. Целью данной работы было исследование этих факторов. Установлена природа термических канавок травления.